Challenged Solving in Listening Through T-Mobile Learning Model - H Setyawan, Wawan; ., Rusijono; ., Nurdyansyah; Budiman, Agus; ., Harianto; Sumarno, Alim; Rais, Pandi (International Journal of Engineering and Technology, 2018)
The Electronic Learning (e-Learning) is one of trend education in Indonesia. Mobile learning is a part of electronic learning or better known as e-learning. Regarding the number of users of mobile devices in Indonesia, mobile learning can be used as an alternative to solve problems. The purpose of the mobile learning program is to facilitate student learning wherever and whenever. Because it has characteristics that are pre-practically carried everywhere, mobile learning has its own interests. Therefore, the researchers develop effectiveness mobile-based learning for student problems as the answer to the challenges of the curriculum in Indonesia and to the development of the contemporary model to help students and educators to learn more easily at least to provide student learning motivation. The T-Mobile Learning Model aims to provide a practical knowledge in conducting problem-based learning model on a listening subject that is relevant to the current problems, especially for a new student of the education faculty at Universitas Islam Kadiri. The result shows that the Model can improve the learning in a listening subject which its implementation has been integrated into the special theme from the test scores and students' result.Â